Mechanisms of complement resistance induced by non-lethal complement attack and by growth arrest. - Marchbank, K J (1997)
Non-lethal complement (C) attack on K562 cells has been shown to induce a transient resistance to lethal amounts of C. We have previously shown that incubation of K562 with phorbol 12-myristate 13-acetate (PMA) caused an increase in both CD59 expression and resistance to C killing and we were interested to examine whether non-lethal C attack caused a similar effect. We here demonstrate that expression of the C inhibitors decay-accelerating factor (DAF), membrane cofactor protein (MCP) and CD59 was unaltered on K562 after non-lethal C attack and that neutralization of these inhibitors with specific blocking antibodies did not reverse the induced resistance. In an effort to understand the mechanisms of resistance we searched for other conditions that might induce C resistance in K562 cells. Growth-arrested cells showed a similar degree of resistance to C killing. The levels of DAF and MCP on these cells were unaltered whereas expression of CD59 was markedly reduced. Non-lethal C attack on these growth-arrested cells induced a further increase in resistance to C killing, suggesting that the mechanisms of resistance were not identical. Indeed, resistance of non-lethally attacked cells was completely lost within 8 hr of attack whereas resistance of growth-arrested cells was detectable for up to 48 hr after returning to cell cycle. These data demonstrate that C resistance induced by two distinct strategies is not mediated by the known membrane C inhibitors. Resistance may be a result of the expression of a novel inhibitor or due to metabolic depletion, a likely common consequence of non-lethal C attack and induction of growth arrest, implying that cells take an active role in C-mediated killing.